Organizational Theory at the Crossroads: Some Reflections on European and United States Approaches to Organizational Research - Koza, Mitchell P.; Thoenig, Jean-Claude (Organization Science, 1995)
Organizational research in Europe and the United States differs in style and substance. Viewed comparatively, important inter-continental differences persist in theory, method, and problem. However, viewed longitudinally, convergence of the two traditions over the last decade is striking. Forces for the historic separation and contemporary convergence of European and United States organizational theory derive from changing instutitional patterns affecting the social location, training, mobility, and rewards of scholars on the two continents.